2023
DOI: 10.1371/journal.pone.0283143
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of time to death among preterm neonates admitted to neonatal intensive care units at public hospitals in southern Ethiopia: A cohort study

Alo Edin Huka,
Lemessa Oljira,
Adisu Birhanu Weldesenbet
et al.

Abstract: Background Although the survival of preterm neonates has improved, thanks to advanced and specialized neonatal intensive care, it remains the main reason for neonatal admission, death, and risk of lifelong complication. In this study, we assessed time to death and its predictors among preterm neonates admitted to neonatal intensive care units (NICU) at public hospitals in southern Ethiopia. Methods A hospital based retrospective cohort was conducted among preterm neonates admitted to NICU at public hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
0
1
Order By: Relevance
“…In this study, preterm neonates born from mothers who had an obstetric complication during their current pregnancy had a higher hazard of neonatal death compared to their counterparts. This finding is comparable with studies reported from Addis Ababa [ 12 ] and Southern Ethiopia [ 17 ]. This might be explained by the fact that obstetric complications affect the pregnancy status and placental blood transfusion, and can result in preterm delivery with subsequent preterm-related life-threatening complications which might increase the hazard of neonatal death.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, preterm neonates born from mothers who had an obstetric complication during their current pregnancy had a higher hazard of neonatal death compared to their counterparts. This finding is comparable with studies reported from Addis Ababa [ 12 ] and Southern Ethiopia [ 17 ]. This might be explained by the fact that obstetric complications affect the pregnancy status and placental blood transfusion, and can result in preterm delivery with subsequent preterm-related life-threatening complications which might increase the hazard of neonatal death.…”
Section: Discussionsupporting
confidence: 91%
“…Partly, this disparity might result from a difference in sample size, study design, and those reported studies were multicenter studies. Conversely, this study finding is lower than studies reported from India 33.5% [ 33 ], Southern Ethiopia 47.7 deaths per 1,000 neonatal days [ 17 ], Mizan Tepi 62.15 deaths per 1,000 neonate-days [ 13 ] and Jimma, Ethiopia 34.9% [ 28 ]. This discrepancy might result from variation in study design as a study reported from India was a multicenter prospective study conducted on a large sample size.…”
Section: Discussioncontrasting
confidence: 80%